Breve crónica sobre o proceso de normalización e a situación social da lingua galega - Muñoz Carrobles, Diego (Madrygal. Revista de Estudios Gallegos, 2009)
In this article we are going to have a look at the normalization process of Galician and its progress during the last thirty years, taking into account the main dates and events happened in this period of time. We will shortly describe the current sociolinguistic situation and the challenges that the Galician language has to face to reach its effective normalization.